POLITICAL RELATIONS BETWEEN SERBIA AND PORTUGAL AT THE BEGINNING OF THE 21ST CENTURY - Petrović, Rajko Č. (National interest, 2023)
The subject of research in this paper is the political relations between two geographically distant countries, Serbia and Portugal, at the beginning of the 21st century, that is, in a precisely defined time period from 2001 to 2022. The starting assumption is that Serbia and Portugal, despite the fact that they established official diplomatic relations at the end of the 19th century, today do not have sufficiently developed political ties, primarily due to a mutual lack of interest in developing them. The goals of the research are aimed at examining the level of development and the quality of political relations between the two countries, subjective and objective obstacles to their realization, as well as perspectives and opportunities for raising them to a higher level in the future. The results of the research confirmed the initial hypothesis, contributing at the same time to the study of the relationship between Serbia and Portugal in terms of systematization and description of what has been achieved so far in that area. The conclusion that emerges is that, due to Portugal’s attitude towards the issue of independence оf the so-called Kosovo, this country’s relations with Serbia can hardly be rated as good, and in the future, limited developments in the framework of economic cooperation between the two countries can be expected in the context of the continuation of the European integration processes in Serbia, but not in the field of political relations. During the research, we used the historical method, the case study method, the analysis method and the comparative method.